Application of structurated materials: catalysts, supports and gas difusion layer in pem fuel cells. - Bruno, Mariano; Franceschini, Esteban; Thomas, Yohann; Corti, Horacio; Roberti, Mariano; Fraigi, Liliana (Revista Ciências Exatas, 2009)
Pronton Exchange Membrane Fuel Cells (PEMFCs), i.e. hydrogen or methanol, showed that several processes were affecting its efficiency in addition to the intrinsic characteristics of the materials used. The inlet of the fuel, the outlet of the oxidation products, the catalyzer electroactive area are some of the points that can be improved with the use of structured materials. This work will focus on the integration of the anodic part (diffusion layer – support – catalyzer) in a PEMFC. In the first part, the work focused on adapting and optimizing meso-porous catalyzers that will be used in a DMFC (Direct Methanol Fuel Cell). The reduction of platinium salts dissolved in the aqueous regions of the surfactants crystaline phases was used as a way for the formation of porous catalyzers with a system of pores lined up and periodically separated. The thickness of the deposited metal was improved in order to reach the best catalytic area with the smallest mass of platinium. These materials were charaterized superficially and electrochemically by SAXS (Small Angle X-Ray Scattering) and refectometry. Secondly, the monolithic carbon with a hierarchical pore structure was used as a gas diffusion layer, which also acted as a catalyzer support. Moreover, the optimization of the product transport was studied via the mechanization of the material. This process of integration can improve the miniaturization of the system and will be a powerfull help for small portable devices. Key words: Mesoporous, Catalizer, Mesoporous Carbón, DMFC